Pakistan : Eighth Review Under the Extended Arrangement and Request for Waivers of Nonobservance of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Pakistan. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses Pakistan's Eighth Review Under the Extended Arrangement and Request for Waivers of Nonobservance of Performance Criteria (PC). Two end-June 2015 quantitative PCs and three indicative targets were missed, but deviations were either minor or temporary and corrective actions have been taken as needed. The authorities remain on track to meet the end-September 2015 program targets. Although the program's monetary PCs were met, the PCs on the fiscal deficit and government borrowing from the central bank were missed. The end-September structural benchmark (SB) to improve the central bank's interest corridor and the end-November SB to enact the Credit Bureau Bill were met ahead of time.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet